Shame in patients with psychogenic nonepileptic seizure: A narrative review. (January 2022) - Reuber, M; Roberts, Nicole A.; Levita, Liat; Gray, Cordelia; Myers, Lorna
Highlights: PNES have been linked to dysregulated emotions and arousal. Chronic shame, shame proneness and dysregulation are key problems in PNES. Shame may be a predisposing, precipitating, perpetuating or trigger factor. Shame may explain much of the phenomenology of PNES. There is overlap of the neurobiology of shame and PNES. Abstract: Psychogenic Nonepileptic Seizures (PNES) have been linked to dysregulated emotions and arousal. However, the question which emotions may be most relevant has received much less attention. In this multidisciplinary narrative review, we argue that the self-conscious emotion of shame is likely to be of particular importance for PNES. We summarize current concepts of the development of shame processing and its relationship with other emotional states. We demonstrate the potential of acute shame to cause a sudden disruption of normal cognitive function and trigger powerful behavioral, cognitive, physiological and secondary emotional responses which closely resemble key components of PNES. These responses may lead to the development of shame avoidance strategies which can become disabling in themselves. We discuss how excessive shame proneness and shame dysregulation are linked to several psychopathologies often associated with PNES (including depression and PTSD) and how they may predispose to, precipitate and perpetuate PNES disorders, not least by interacting with stigma. We consider current knowledge of the neurobiological underpinnings of shame and PNES. We explore how shame could be the link between PNES and a heterogeneous range of possible etiological factors, and how it may link historical aversive experiences with individual PNES events occurring much later and without apparent external trigger. We argue that, in view of the potential direct links between shame and PNES, the well-documented associations of shame with common comorbidities of this seizure disorder and the well-characterized relationship between chronic shame and stigma, there is a compelling case to pay greater attention to shame in relation to PNES. Its role in the treatment of patients with PNES is discussed in a separate, linked review incorporating case vignettes to highlight the complex interactions of different but interlinked shame-related issues in individual patients